International loans, bonds, guarantees, legal opinions - Wood, Philip (Philip R.), 1942-; Wood, Philip (Philip R.), 1942- (London : Sweet & Maxwell, 2007)
This volume provides coverage of syndicated bank credit agreements and loan transfers, international bond issues including equity-linked bonds, note programs and high yield notes, bondholder trustees and collective action clauses and more.
Introduction to term loans and syndicated credits -- Types of credit facility -- Financial terms of syndicated credit agreements -- Representations and warranties -- Covenants -- Events of default -- Agency, syndicate democracy, transfers and other clauses -- Outlines of credit agreement documents -- Loan transfers and participations -- Bond issues: general principles -- Negotiability of bonds and clearing systems -- Terms of bonds -- Convertible and other equity-linked bonds -- High yield notes -- Other special types of bond issue -- Bondholder trustees and meetings -- Syndicate agents and bondholder trustees as fiduciaries -- Introduction to guarantees -- Terms of guarantees -- Independent guarantors: bank and export credit guarantees -- Stand by letters of credit -- Other forms of guarantee -- Comfort letters -- Outlines of guarantees -- Introduction to legal opinions -- Terms of legal opinions -- Outlines of legal opinions.
Revised edition of: International loans, bonds, and securities regulation / by Philip R. Wood.
Includes bibliographical references and index.
Keywords: Loans, Foreign -- Law and legislation; Bonds -- Law and legislation; Syndicated loans -- Law and legislation; Letters of credit; Suretyship and guaranty -- Law and legislation; Pledges (Law); x; Obligations (Valeurs) -- Droit; x; Cautionnement -- Droit; Finances internationales; 2; 2; Droit financier; Emprunts internationaux; Garanties; 2; 2; Bonds -- Law and legislation; Loans, Foreign -- Law and legislation; Pledges (Law); Syndicated loans -- Law and legislation; Letters of credit; 2; Effecten; Obligaties; Effectenrecht; 2